Pencegahan Korupsi Melalui Pendalaman Karakter Dalam Model Pendidikan Anti Korupsi Di Perguruan Tinggi - Nyoman Asri Mahadhyaksa (Ganesha Civic Education Journal, 2022)
Efforts of a judicial nature such as reforming the legal system in dealing with criminal acts of corruption have proven to be lacking in creating an optimizing awareness of unlawful acts for individuals who are fond of committing corruption, because within teh perpetrators of corruption are instilled a mindset that is materialistic and egotistical. Therefore instead of continuing to update the legal system related to corruption, it is better to fix the small things that can cause individuals to have a desire for corruption. One of them is the improvement of character education which is also supported by anti-corruption education. As agents of change and elements of society, students must be equipped with character education and anti-corruption education so that they can foster an anti- corrup mindset. The purpose of this research to explore efforts that can be made to minimize corruption through deepening character education in the anti-corruption education model in tertiary institutions, where this research uses descriptive analysis based on library materials.